(untitled) (Far Western Review, 2024)
This paper tries to investigate the cause of the rapid growth of private schools and decline of public schools. The researcher has used qualitative, descriptive and explanatory methods to identify the problem statement. The research shows that the public schools are established by the government itself as well as by the community themselves. All the funding and budgetary aspects are being fulfilled by the government and the infrastructures are well equipped after the earthquake occurred in 2072 B S. Private schools are almost financed, controlled and operated by private sectors so that quality of the education is being strictly maintained in comparison to public schools for the retaining the students. Private schools always survive in fear of students whereas public schools have no pressure of student admission. Private schools are the choice of the parents due to the language of instruction that is English. In the public schools, they are having good infrastructure in urban area after massive earthquake, book free Friday, day food program, English medium classes are the major impressive factors for the students. There is a huge gap in the educational system in public schools and private schools in respect of its result, caring for students, parents’ involvement, ECA/CCA activities etc. This study indicates that the duality educational systems through public and private schools works effectively by the public private partnership in PPP model. The government should develop a regulatory body which makes the investment of the private sector secure, make the teachers secure in his/her retirement life by pension, arranging training program for the teachers, controlling the academic drawbacks as compared to public schools.